La signoria rurale nell’Italia del tardo medioevo. 6 Le signorie trentine (Firenze University Press, 2023)
In recent decades, the importance of rural lordship in the history of Italy in the late Middle Ages has been reconsidered and reassessed. On the basis of a wealth of archive documentation, this volume offers a systematic and reasoned description of the political, economic, social and cultural aspects of rural lordship in a territory located “on the borders of Italy'” the episcopal principality of Trento in the 14th and 15th centuries. From their castles scattered in the alpine valleys, at the foot of the mountains, the noble families of Trento looked increasingly towards Vienna and the Habsburg empire; in their relations with the peasant world, they set up in the 15th century balances of power destined to remain almost intact throughout the modern age, until the end of the First World War.